PERFORMANCE ANALYSIS OF EXTERNAL BALLISTIC WITH DRAG MODEL VARATION FOR THREE DIMENSIONAL SHOOTING SIMULATORS - (NIM 23207081), ALAMSYAH
External ballistic is part of ballistic science that deals with projectile behavior in flight. External ballistic includes all forces that affect projectile behavior when flight together with other aspect such as muzzle velocity, shooting angle and projectile's spin rate. One of the forces that have greater effect to projectile behavior which is described by its trajectory is drag force. Drag is a force that exists because of fluid resistance to projectile that moves with a certain velocity. Projectile's drag characteristic is obtained by multiplying projectile's form factor with with G1 standard drag function. In this research, G1 drag function is modeled using regression function for a certain range of velocity and implemented in shooting simulator software. Research will also evaluate the accuracy of model in simulator by comparing the research result with the actual data based on trajectory table from the ammunition maker. For the implementation of simulator system, Irrlicht 3D Engine is used to build the virtual environment and C++ language is used to write the program. Research's results show that model of G1 drag function works well for a projectile's velocity above 340 m/s while results for velocity under 340 m/s give a significant calculation's error.